(untitled) (Baghdad Science Journal, 2024)
A series of new heterocyclic derivatives A5-A15 have been synthesized using 4-(toluene-4-sulfinylamino)-benzoic acid ethyl ester A2 as a predecessor. This compound A2 was successfully used in synthesis of some new derivatives of oxadiazole, pyrazole, triazole, thiadiazole, thiazole and fused heterocyclic containing p-toluene sulfonamide moiety that supposed to have important biological activities. 1H-NMR, 13C-NMR and FT-IR spectroscopy were used to confirm the prepared compounds.